Regional Cooperation in South Asia
X, 368 p. 30 illus. in color.
Keywords: This book highlights various challenges and opportunities for regional cooperation and development in South Asia. In light of the ongoing globalization process, the contributors investigate how socio-economic developments are changing the spatial organization of production as well as the profile of cities and landscapes, are stimulating the creation of maritime, terrestrial and aerial channels, and are putting increasing pressures on natural and environmental resources. The book is divided into four parts: The first part analyses the increasing intensity of regional trade, migration and investment flows; the second focuses on channels and adapted spaces. The third part addresses sustainability and natural resources, while the fourth highlights institutional issues. .